2021
DOI: 10.1002/ldr.3942
|View full text |Cite
|
Sign up to set email alerts
|

Understory removal accelerates nucleic phosphorus release but retards residual phosphorus release in decomposing litter of Phyllostachys edulis in subtropical China

Abstract: Despite the importance of understory vegetation for ecosystem processes and functions, its contribution to the dynamics of phosphorus (P) fractions in decomposing litter has rarely been studied in subtropical plantations. Herein, by conducting an understory removal (UR) experiment in a moso bamboo (Phyllostachys edulis) plantation of South China, we assessed the effect of understory species on leaf litter mass loss and P fractions (inorganic P, sugar P, nucleic P, and residual P) of moso bamboo over a 12-month… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 39 publications
1
1
0
Order By: Relevance
“…Many other studies have reported that UR improves nutrient availability and promotes microbial growth, as shown by previous research near our site [25]. The existing literature suggests that UR can deliver more inorganic nitrogen (NO 3 − -N and NH 4 + -N) to the soil microbiota [53,54], which indirectly influences these processes.…”
Section: Understory Vegetation Removal Soil Nitrogen Processes and Se...supporting
confidence: 72%
“…Many other studies have reported that UR improves nutrient availability and promotes microbial growth, as shown by previous research near our site [25]. The existing literature suggests that UR can deliver more inorganic nitrogen (NO 3 − -N and NH 4 + -N) to the soil microbiota [53,54], which indirectly influences these processes.…”
Section: Understory Vegetation Removal Soil Nitrogen Processes and Se...supporting
confidence: 72%
“…In forests, the litter layer is a primary P source to plants (Sayer & Tanner, 2010). When understory removal accelerates labile P fraction releases during litter decomposition (Qiu et al, 2021), plants may absorb P from the litter layer instead. Accordingly, soil available P remained unchanged after understory removal.…”
Section: Discussionmentioning
confidence: 99%